2020
DOI: 10.3390/ma13010186
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Recycled High-Performance Aggregate on Deformation and Load-Carrying Capacity of Reinforced Concrete Beams

Abstract: The use of recycled concrete aggregates (RCA) in high performance concrete (HPC) was analyzed. The paper presents the experimental studies of model reinforced concrete beams with a rectangular section using high-performance recycled aggregates. Two variable contents of recycled aggregate concrete were used in this study: 50% and 100%. The experimental analyses conducted as immediate studies concerned the following issues: short time loads-deflection, load-carrying capacity of beams, deformation of concrete, cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 66 publications
(98 reference statements)
3
15
0
Order By: Relevance
“…The graph clearly shows close correlation between the modulus of elasticity and the compressive strength of concrete. This is also confirmed by the previous studies conducted by the authors [30]. Similar conclusions were also drawn by Góra et al [52].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The graph clearly shows close correlation between the modulus of elasticity and the compressive strength of concrete. This is also confirmed by the previous studies conducted by the authors [30]. Similar conclusions were also drawn by Góra et al [52].…”
Section: Resultssupporting
confidence: 92%
“…The chemical composition of the aggregates is presented in Table 4. The data have been taken from a paper published by one of the authors [30].…”
Section: Methodsmentioning
confidence: 99%
“…Similar relationships were found for mortars containing 25%-100% fine RCA [28]. Reduction of compressive and flexural strength and elasticity modulus was also described for HPC containing RCA after 7, 14 and 28 days [26]. Concretes containing 50% and 100% RCA have lower compressive strength compared to control concrete, however, the use of concrete from railway sleepers demolition caused an increase in strength [25].…”
Section: Introductionsupporting
confidence: 64%
“…The absorbability increases from about 5.5% for concrete without RCA to about 8% at 100% replacement level. Increase of absorbability and porosity by 15%-38% and decrease of density by 4%-7% for HPC is described in [26]. Studies described in [25] showed that concretes containing 50 and 100% RCA have a lower density compared to control concrete.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation